2012
DOI: 10.1002/ajh.22274
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thrombospondin‐1 is increased during acute sickle cell vaso‐occlusive events and associated with acute chest syndrome, hydroxyurea therapy, and lower hemolytic rates

Abstract: Platelets are activated in sickle cell disease (SCD), and particularly during vaso-occlusive episodes (VOE). Thrombospondin-1 (TSP1), a major secretory product of activated platelets, is increased in the circulation in VOE and binds to sickle red blood cells (RBC) promoting vascular adhesion. Thus, we hypothesized that TSP1 may represent a plasma biomarker of disease severity in SCD. We tested the plasma collected from patients in steady state (n = 27) and VOE (n = 14), as well as healthy controls (n = 17) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 26 publications
3
80
2
4
Order By: Relevance
“…In patients with hypertension, elevated plasma TSP1 was noted in association with decreased forearm-mediated vasodilation (18). However, in this study, TSP1 levels appeared elevated in controls compared to TSP1 levels reported in controls elsewhere (184), suggesting possible confounding by platelet activation. Nonetheless, elevation of plasma TSP1 in individuals with hypertension has been confirmed (80,241), although interpretation of these other studies is complicated by the presence of other cardiovascular comorbidities.…”
Section: A Redox Signaling In Stem Cellscontrasting
confidence: 71%
See 3 more Smart Citations
“…In patients with hypertension, elevated plasma TSP1 was noted in association with decreased forearm-mediated vasodilation (18). However, in this study, TSP1 levels appeared elevated in controls compared to TSP1 levels reported in controls elsewhere (184), suggesting possible confounding by platelet activation. Nonetheless, elevation of plasma TSP1 in individuals with hypertension has been confirmed (80,241), although interpretation of these other studies is complicated by the presence of other cardiovascular comorbidities.…”
Section: A Redox Signaling In Stem Cellscontrasting
confidence: 71%
“…Tempol can inhibit the Fenton reaction, a source of hydroxyl radical that limits arterial vasodilation (263). This may be clinically relevant in conditions of dysregulated iron metabolism such as sickle cell disease wherein Fenton chemistry and circulating TSP1 are enhanced (184,203).…”
Section: B Tsp1 and Ros Signaling In Vascular And Renal Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the proadhesive protein thrombospondin 1 (TSP1) was recently reported to inhibit NO signaling 23,24 while promoting PAH in preclinical models 25 and to be upregulated in SCD patient plasma. 26 Although studies have documented the hemodynamics and outcomes of SCD-associated PAH and interrogated the systemic vascular function of these patients, there have been no human studies directly evaluating the pulmonary vasculature. We herein describe ex vivo benchtop profiling that includes molecular, cellular, mechanical, genetic, and functional signatures of the explanted SCDassociated PAH lungs from a patient who underwent successful lung transplantation.…”
Section: Introductionmentioning
confidence: 99%